Comparable Evaluation of Nutritional Benefits of Lactobacillus plantarum and Bacillus toyonensis Probiotic Supplementation on Growth, Feed Utilization, Health, and Fecal Microbiota in Pre-Weaning Male Calves - Mohamed S. Ayyat; Hamdy A. El-Nagar; Wael M. Wafa; Khaled M. Abd El-Latif; Samir Mahgoub; Adham A. Al-Sagheer (Animals, 2023)
This study was conducted to investigate the impact of probiotic supplementation using Lactobacillus plantarum DSA 20174 and/or Bacillus toyonensis ATCC 55050 on growth performance, blood parameters, hematological measures, and fecal microbiota in pre-weaning Holstein calves. Thirty-two four-day-old male calves with a similar genetic background, weighing an average of 38.27 ± 0.12 kg, were randomly assigned to four groups. The groups consisted of a control group (CON) without supplementation, a group receiving B. toyonensis (BT) at 3 × 109 cfu/calf/day, a group receiving L. plantarum (LP) at 1 × 1010 cfu/calf/day, and a group receiving a combination of LP and BT (LP + BT) at half the dosage for each. The study found that calves supplemented with LP and LP + BT experienced significant improvements in average daily gain and final body weight compared to the control group. The LP + BT group showed the most positive effects on TDMI, starter intake, and CP intake. RBC counts tended to be higher in the probiotic groups, with the LP + BT group having the highest values. The LP + BT group also had higher total protein, albumin, globulin, and hematocrit concentrations. All probiotic groups showed higher serum IgG concentrations. Probiotic supplementation led to increased total bacterial count and decreased levels of E. coli, salmonella, and clostridium. The LP + BT group had a significant decrease in coliform count, while both LP and LP + BT groups had increased Lactobacillus populations. In conclusion, LP + BT probiotic supplement showed the most beneficial effects on growth, feed efficiency, blood constituents, and modulation of fecal microbiota composition.